Climate and aeroallergen levels in asthma: a 12 month prospective study. Issue 6 (June 1997) - Epton, M J; Martin, I R; Graham, P; Healy, P E; Smith, H; Balasubramaniam, R; Harvey, I C; Fountain, D W; Hedley, J; Town, G I
Abstract : BACKGROUND: There is evidence to suggest that changes in weather and airborne fungal spore and pollen counts may affect asthma symptoms. METHODS: The relationship between climate, airborne fungal spore, and pollen counts and peak expiratory flow rate (PEFR) and asthma symptoms was prospectively investigated in a population of mild to moderate asthmatic subjects in Blenheim, New Zealand. Subjects recorded twice daily PEFR measurements and asthma symptom scores for up to one year. Spore and pollen counts were measured two hourly and meteorological data were measured hourly. Individual, within person, multiple linear regression analyses were conducted, adjusting for auto-correlation. A random effects model was assumed for the individual regression co-efficients and weighted estimates of the mean of these coefficients were obtained by the method of maximum likelihood. RESULTS: One hundred and thirty nine asthmatic patients (60% atopic) aged 17-80 years completed the study. Of the weather variables, only temperature showed a small but consistent association with PEFR. The mean rise in PEFR for an 8.8 degrees C (2 SD) change in temperature was 0.78% (95% CI 0.44% to 1.11%), approximately 3.0 l/min. There was a weak association between days of high basidiospore counts and increased nocturnal wakening and reliever medication use. Pollen counts showed no consistent association with either PEFR or asthma symptoms. CONCLUSIONS: The results of this study suggest that the effects of weather and aeroallergens on PEFR and asthma symptoms in this population are small, and that other causes need to be sought to account for variations in asthma severity and exacerbations.